Trends and Themes in Local History Research in Indonesia (2000–2025): A Scoping Review and Bibliometric Analysis - Muhammad Junaldi Jufri Jufri; Aldi Hendra Pratama Pratama; Roro Wilis Wilis; Bonita Padang Padang; Ajeng Diah Kinanti Kinanti; M Budiman Budiman (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
This study aims to map the development of trends and themes in local history research in Indonesia during the period 2000–2025 through a scoping review and bibliometric analysis. Data were collected from three main databases, namely Scopus, Crossref, and Google Scholar. Through a process of identification, screening, and selection based on inclusion and exclusion criteria, 383 articles were obtained for further analysis. The analysis was conducted to identify publication trends, theme distribution, and patterns of interrelationships between topics using keyword co-occurrence analysis. The results showed that local history studies in Indonesia experienced a significant increase, peaking in 2025 with 59 publications. Nine main themes dominate, namely: 1) Culture, Traditions, and Local Identity, 2) Education and Local Intellectuals, 3) Social and Community Life, 4) Environment and Space, 5) Local Politics and Power, 6) Religion and Beliefs, 7) Gender and Marginalized Groups, 8) Economy and Livelihoods, and 9) Local Contemporary History. Co-occurrence analysis through keyword network visualization shows four interconnected theme clusters, indicating conceptual integration in the development of local historiography. However, this study has limitations in its database coverage, and its analysis focused on metadata. Therefore, further studies are recommended to expand the literature sources and conduct more in-depth content analysis to enrich the understanding of the direction of local historical development in Indonesia.